Assessment of Clinical Skills Competency Among Final-Year Medical Students in Pakistan: A Cross-Sectional Study - Muhammad Amjad, Abdul Munim, Muhammad Ali Haider, Noor-un-Nisa Memon, Arsala Zaman, Mian Bilal Ahmad, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Clinical skills competency amongmedical graduates represents a fundamentaldeterminant of future healthcare quality, yetglobal concern persists regarding variability